PASAR MODAL SYARIAH SEBAGAI INSTRUMEN INVESTASI DI INDONESIA DALAM TINJAUAN MASLAHAH - Bachrul Ulum; Maulani Muqirroti Ainil Ma’rifah; Miftahul Jannah (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2026)
Abstract The Islamic capital market is an integral part of the Islamic financial system that operates based on sharia principles, such as the prohibition of riba, gharar and maysir, and emphasizes fairness, transparency and economic sustainability. The purpose of this article is to analyze the role of functioning as an investment instrument that is in accordance with the principle of maslahah in the context of Islamic finance in Indonesia. The contribution of the Islamic capital market to the economic well-being of society, along with the possibilities and problems it faces, are examined in this study using qualitative descriptive analysis. The study comes to the conclusion that, from an economic and social standpoint, Indonesia's Islamic capital market has shown a strong alignment with the maslahah principles. The expansion of the Islamic capital market has also been aided by the recognition of the primacy of the legislation controlling capital market activities. Along with the advantages for the parties involved, this will promote economic expansion in line with the expansion of Indonesia's Islamic capital market. Keywords: Maslahah, Islamic Capital Market, Instrument Instruments